1991
DOI: 10.1126/science.1990444
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Sequence and Structural Elements in the HIV-1 Principal Neutralizing Determinant: Corrections and Clarifications

Abstract: This communication serves to correct and clarify several points in the report "Conserved sequence and structural elements in the HIV-1 principal neutralizing determinant" by G. J. LaRosa et al. (24 Aug., p. 932) [Science 249, 932 (1990)]. The corrections are as follows. In figure 1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
1
8
1
Order By: Relevance
“…In the context of sexual transmission, the type of sexual encounter, gender of the transmitter and recipient, nature of the mucosal surface and presence of other genital tract infections can all play an integral role in selection during transmission. In order to distinguish the presence or absence of viral variants, the highly variable sequences of HIV-1 envelope (env) have been used as markers of diversity, especially in the V1-V2 and V3 regions of env which are important for immune recognition (Clerici et al 1991;Javaherian et al 1990;LaRosa et al 1991), replication effi ciency (Takeuchi et al 1991) and cellular tropism (Chesebro et al 1991;de Jong et al 1992;Hwang et al 1991;O'Brien et al 1990;Shioda et al 1991;Westervelt et al 1991;Westervelt et al 1992) and are under constant selection, resulting in a high rate of variation (Delwart et al 1994;Delwart et al 1993;Holmes et al 1992;Javaherian et al 1990;Kuiken et al 1993;Wang et al 1995;Zhu et al 1993). Due to the increased variability, these regions have been used extensively to characterize the level of heterogeneity in donor/recipient HIV-1 transmission events.…”
Section: Transmission and Selection Of Variantsmentioning
confidence: 99%
“…In the context of sexual transmission, the type of sexual encounter, gender of the transmitter and recipient, nature of the mucosal surface and presence of other genital tract infections can all play an integral role in selection during transmission. In order to distinguish the presence or absence of viral variants, the highly variable sequences of HIV-1 envelope (env) have been used as markers of diversity, especially in the V1-V2 and V3 regions of env which are important for immune recognition (Clerici et al 1991;Javaherian et al 1990;LaRosa et al 1991), replication effi ciency (Takeuchi et al 1991) and cellular tropism (Chesebro et al 1991;de Jong et al 1992;Hwang et al 1991;O'Brien et al 1990;Shioda et al 1991;Westervelt et al 1991;Westervelt et al 1992) and are under constant selection, resulting in a high rate of variation (Delwart et al 1994;Delwart et al 1993;Holmes et al 1992;Javaherian et al 1990;Kuiken et al 1993;Wang et al 1995;Zhu et al 1993). Due to the increased variability, these regions have been used extensively to characterize the level of heterogeneity in donor/recipient HIV-1 transmission events.…”
Section: Transmission and Selection Of Variantsmentioning
confidence: 99%
“…Neutralization of HIV-1 JRcsf demonstrated that the B/E vaccine could neutralize a prototypic CD4-resistant, CCR5-dependent, macrophage-tropic virus. Neutralization of the Brazilian isolate BZ167 demonstrated that the bivalent formulation could elicit antibodies able to neutralize a syncytiuminducing, T-cell-tropic, subtype B, primary isolate that differed from MN in the V3 domain subtype B consensus PND sequence (i.e., IRIGPGRTF rather than IHIGPGRAF) (22). Similar results were obtained with the Thai BЈ iso-late, TH92014, and the T-cell-tropic Thai E isolate, 302051, both of which differed from MN-rgp120 and A244-rgp120 at the V3 domain crown sequence ( Table 2) yet were neutralized, albeit at low titers, by the bivalent B/E antisera.…”
Section: Neutralization Of Diverse Primary Isolates With Antisera To mentioning
confidence: 99%
“…Molecular epidemiologic studies have defined approximately nine genetically distinct subtypes of HIV-1 (33). In some geographic regions (e.g., sub-Saharan Africa) multiple subtypes (e.g., A, C, D, G, and O) of HIV-1 are in circulation (32,36), whereas in other geographic regions (e.g., United States, western Europe, Thailand) the representation of genetic subtypes is more restricted, with the majority of infections limited to a single subtype (e.g., B or E) (19,22,33,40). Because amino acid sequence variation in the envelope glycoproteins varies from 25 to 30% between subtypes, it has been speculated that multivalent vaccines, containing viral antigens from several genetically distinct viruses, will be required for vaccines to provide protective immunity against all of the genetic subtypes circulating in human populations.…”
mentioning
confidence: 99%
“…The third hypervariable (V3) domain of gp120 is a disulfide-linked loop of approximately 40 amino acids with a high degree of sequence diversity among different viral isolates [4][5][6]. The V3 loop is one of the major immunogenic sites on the virus and is sometimes called the principal neutralizing determinant (PND) [7].…”
Section: Introductionmentioning
confidence: 99%